1989
DOI: 10.1042/bj2610945
|View full text |Cite
|
Sign up to set email alerts
|

Rapid stimulation of hepatic oxygen consumption by 3,5-di-iodo-l-thyronine

Abstract: Tri-iodothyronine (T3) and thyroxine (T4) as well as 3,5-di-iodothyronine (T2) stimulated O2 consumption by isolated perfused livers from hypothyroid rats at a concentration as low as 1 pM by about 30% within 90 min. Application of T2 resulted in a faster stimulation than with application of T3 or T4. Inhibition of iodothyronine monodeiodinase by propylthiouracil, thereby blocking the degradation of T4 to T3 and of T3 to T2, demonstrated that only T2 is the active hormone for the rapid stimulation of hepatic O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 41 publications
(61 reference statements)
2
75
0
2
Order By: Relevance
“…The ability of THs to regulate energy utilization as well as their role in promoting mitochondrial uncoupling of substrate oxidation from ATP synthesis have been long recognized. T 2 , as T 3 , was shown to rapidly stimulate hepatic O 2 uptake when injected in perfused livers (Horst et al 1989), or added to mitochondria isolated from hypothyroid rats (Moreno et al 2002). Similar effects of T 3 have been observed in hepatocytes isolated from hypothyroid animals (Nobes et al 1990).…”
Section: Discussionsupporting
confidence: 52%
“…The ability of THs to regulate energy utilization as well as their role in promoting mitochondrial uncoupling of substrate oxidation from ATP synthesis have been long recognized. T 2 , as T 3 , was shown to rapidly stimulate hepatic O 2 uptake when injected in perfused livers (Horst et al 1989), or added to mitochondria isolated from hypothyroid rats (Moreno et al 2002). Similar effects of T 3 have been observed in hepatocytes isolated from hypothyroid animals (Nobes et al 1990).…”
Section: Discussionsupporting
confidence: 52%
“…We have excluded both selective TR interactions and discrepancies between standard in vitro assays of ligand binding and TR function as potential mechanisms. Previous studies have raised the possibility that T 2 may have extra-nuclear effects, independent of classical nuclear TRs (Horst et al 1989, Kvetny 1992, Lanni et al 1993, Goglia et al 1994. Both GH and TSH mRNA levels can be regulated at a posttranscriptional level by T 3 (Jones et al 1990, Krane et al 1991.…”
Section: Discussionmentioning
confidence: 99%
“…potency of T 3 in anti-goitre assays in vivo (Stasilli et al 1959). However, T 2 has rapid and specific effects on oxidative metabolism in rat liver and in mononuclear blood cells (Horst et al 1989, Kvetny 1992, Lanni et al 1992, Goglia et al 1994. T 3 regulates gene expression through TR interaction with TREs located in the promoter region of target genes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in spite of several reports showing rapid effects of triiodothyronine (T3) on mitochondria, the occurrence and the physiological significance of these effects is a long standing controversial issue of thyroid hormone action. In recent years, however, several reports have shown that two diiodothyronines (3,3'-T2 and 3,5-T2), under certain conditions, are the only iodothyronines which rapidly stimulate in vivo and in vitro mitochondrial respiration or cytochrome oxidase (COX) activity [1][2][3][4][5][6]. At the moment, the physiological significance of these effects is not clear and no insight into the mechanism by which diiodothyronines stimulate mitochondrial energy metabolism is available.…”
Section: Introductionmentioning
confidence: 95%